New Options for Improving DAPT and Stent Implantation - Jacobson, Anne (MD Conference Express, 2011)
Stent thrombosis remains an important concern, following percutaneous revascularization in patients with obstructive coronary artery disease. This article describes options for improving the safety of coronary stenting.